Tradução, transcriação e feminismo negro em Alice Walker - Bastos, Camila Rodrigues (2017)
The present research investigates the different forms of translation in the narratives of Alice Walker, analyzing the process of interlingual and cultural translation of the works The Color Purple and The Temple of My Familiar, as well as the intersemiotic translation of the book: The Color Purple. The choice of the object of analysis was based on the desire to ascertain Walker's writing of denunciation, which seeks to subvert the woman's position as being dominated, through a "womanist" perspective, realized through black feminism. In the first chapter it is possible to verify the marks of the postcolonial literature, since the narratives fictionalize questions such as: identity, sexism, racism, misogyny, nature exploration, memory and myth, decolonizing the narrative, through a counterhegemonic attitude, Investigates indigenous and African cultures, as well as the cultural hybrids that originate mestizo characters, subjects of interlacing. The second chapter examines the interlinguistic translation and, finally, the third examines the intersemiotic translation of the novel The Color Purple for the cinema. For this, it is used theorists who study black feminism, translation theories and the postcolonial literature such as Bonnici (2002), Spivak (2000), Bakhtin (2009), Velasco (2012), Bhabha (2002) , Said (1995), Canclini (1990), Walsh (2008), Beauvoir (1969), Hooks (2000), Butler (1990), Newmark (1987), Octavio Paz (1971), Campos ), Stam (2000), Diniz (2005), et al. Thus, it was found that the interlingual translation of English into Portuguese and into Spanish was domesticated, since translators failed to translate the non-standard variety of blacks from the southern United States into their respective languages. In relation to the film transcription, Steven Spielberg seeks to be faithful to the novel, adapting to the film issues such as black feminism, Celie and Nettie loyalty, Celia and Shug Avery's homosexual relationship, and the empowerment of Celie.